THE CORRELATION BETWEEN PHYSICAL WORK ENVIRONMENT AND FATIGUE LEVEL ON THE PACKAGING PRODUCTIVITY OF THE REPETITIVE TASK IN SITTING POSITION - Renny Septiari (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2020)
The packaging is one of the industrial tasks in beverage an industry which is repetitive and monotonous with the same position throughout the day. In order to complete the packaging process, the workers do the tasks in sitting position during one work shift. Sitting position at work is commonly applied in both service and manufacturing industry. This position is mostly applied because it is considered to make a worker feel comfortable in finishing the task. Being supported by a comfortable physical work environment, a worker may sit in long hours during the workday. The aim of the study was to determine the level of productivity of the task done in the prolonged sitting position and affected by the work environment and level of fatigue. With software of SPPS 22 using analysis double correlation test, it was obtained that the value of Sig. F Change 0.027. The software analysis showed that the physical work environment and fatigue influenced packaging productivity significantly. R (the value of Pearson Correlation) obtained was 0.742 which means that there is a strong correlation between free variable (X) and bound variable (Y).R (the value of Pearson Correlation) obtained was 0.742 which means that there is strong correlation between free variable (X) and bound variable (Y).